Sacred interests : the United States and the Islamic world, 1821-1921 - Walther, Karine V. (The University of North Carolina Press, 2015)
"In Sacred Interests, Karine V. Walther excavates the deep history of Americans' Islamophobic fixation on how Muslims should be governed, controlled, converted, and colonized, showing how these ideas shaped American foreign relations from the early republic to the end of the Armenian Genocide in 1921. Beginning with the Barbary Wars, Walther illuminates reactions to and involvement in the breakup of the Ottoman Empire, the efforts to protect Christians and Jews from Muslim authorities in Northern Africa, colonization of the Philippines, and the Armenian Genocide. Even in instances where the U.S. government was not formally involved, American missionaries and activists played crucial roles in these events, drawing conclusions and lessons that they would pass on and apply to subsequent interventions. Americans' interest in Islam abroad became critical to a larger American narrative: diplomatic, cultural, political, and religious beliefs about Islam and Muslims hardened and became self-fulfilling as Americans continued to encounter Muslims throughout the nineteenth and early twentieth centuries"--